Let $\vec a, \vec b$ and $\vec c$ be three non-coplanar unit vectors such that the angle between every pair of them is $π/3$. If $\vec a×\vec b+ \vec b×\vec c =p\vec a+q\vec b+r \vec c$, where p, q and r are scalars, then the value of $\frac{p^2+2q^2 + r^2}{q^2}$, is |
2 4 6 8 |
4 |
We have, $\vec a×\vec b+ \vec b×\vec c =p\vec a+q\vec b+r \vec c$ ...(i) Taking dot product with $\vec a$, we obtain $\vec a.(\vec a×\vec b) + \vec a. (\vec b×\vec c) = p(\vec a· \vec a)+q(\vec a·\vec b) +r (\vec a.\vec c)$ $⇒[\vec a\,\,\vec b\,\,\vec c]=p+\frac{q}{2}+\frac{r}{2}$ ...(ii) Taking dot product on both sides of (i) by $\vec b$, we get $\vec b.(\vec a×\vec b)+\vec b. (\vec b×\vec c) = p(\vec b. \vec a)+q(\vec b. \vec b) +r(\vec c.\vec c)$ $⇒0=\frac{p}{2}+q+\frac{r}{2}$ ...(iii) Taking dot product on both sides of (i) by $\vec c$, we get $\vec c.(\vec a×\vec b)+\vec c. (\vec b×\vec c) = p(\vec c · \vec a) +q(\vec c.\vec b) +r (\vec c. \vec c)$ $⇒[\vec c\,\,\vec a\,\,\vec b]=\frac{p}{2}+\frac{q}{2}+r$ $⇒[\vec a\,\,\vec b\,\,\vec c]=\frac{p}{2}+\frac{q}{2}+r$ ...(iv) From (ii) and (iv), we get $p+\frac{q}{2}+\frac{r}{2}=\frac{p}{2}+\frac{q}{2}+r⇒p=r$ Putting $p=r$ in (iii), we get $q=-r$. Thus, we obtain $p=r=-q$ $∴\frac{p^2+2q^2 + r^2}{q^2}=\frac{(-q)^2+2q^2 +(-q)^2}{q^2}=4$ |